Identifying hotel management study program most enhance attributes for international tourism and business institute using conjoint analysis in pandemic era of covid 19 - Ida Bagus Made Wiyasha (Journal of Business on Hospitality and Tourism, 2021)
Identifying the important attributes of a product or service are crucial activities for marketing purposes. The objectives of this research are two folds. First, to identify the important attributes of Hotel Management study Program ( hereafter MPH) offered to students in the pandemic era of COVID 19. Second, based on these research findings the Manajement of International Tourism and Business Institute (hereafter ITBI) has a basis to strengthen these attributes for marketing purposes of MPH study program. To achieve those objectives primary data would be colleted with students of MPH study program semester 1 and  7 as respondents. Prior to distributing questionnaires to students a discussion with the Management of ITBI conducted in an effort to identify important attributes of MPH study program. To achieve the most enhance attributes of MPH study program conjoint analysis would be applied. This study found that overseas on the job training was the most preferred attribute of MPH study program followed by practical facilities quality.